Evaluation of fatty acid synthase in prostate cancer recurrence: SUV of [11C]acetate PET as a prognostic marker. Issue 15 (18th August 2015) - Leisser, Asha; Pruscha, Konstatin; Ubl, Philipp; Wadsak, Wolfgang; Mayerhöfer, Marius; Mitterhauser, Markus; Hacker, Marcus; Kramer, Gero; Shariat, Shahrokh; Karanikas, Georgios; Hartenbach, Markus; Haug, Alexander R.
<x xml:space="preserve">Abstract</x> Aim High levels of fatty acid synthase have shown to correlate with the aggressiveness of prostate cancer. As [11C]acetate exhibits a close correlation with the level of fatty acid synthase, we aimed to assess whether the SUV in [11C]acetate PET serves as a suitable prognostic marker in patients with recurrent prostate cancer. Materials and Methods In 123 consecutive patients, examined between 2010 and 2014, the maximum standardized uptake value (SUVmax) of local recurrences as well as lymph node and bone metastases was measured. Choosing the spleen as a standard for relatively high physiological uptake, a ratio of tumor to spleen uptake (SUVts) was calculated for standardizing the uptake, too. The corresponding initial Gleason scores (GS) and serum‐PSA levels around the time of the performed PET/CT for each patient were retrospectively collected and PSA doubling together with PSA velocity were determined. For further analysis patients were divided with regard to their initial Gleason score (≤3 + 4 and ≥ 4 + 3). The median of PSA velocity was calculated to separate patients with a high and low PSA velocity and Mann–Whitney U or Student's t‐test were used, testing for significant differences. For correlation Spearmen‐Rho test was used. Results PET was positive for recurrence in 82/123 patients. PSA was significantly higher in PET‐positive than in negative patients (5.9 vs. 3.2 ng/ml; P = 0.006). Initial Gleason score did not differ in PET negative and positive patients (P = 0.3), whereas PSA velocity was markedly higher in PET positive patients (0.4 vs. 0.1 ng/ml/month; P = 0.01). Median SUVmax of PET positive patients was 5.23 (mean 5.78; range 0.9–16.8) and meadian SUVts was 0.78 (mean 0.84, range 0.14–2.50). SUVts was significantly higher in patients with high PSA velocity (SUVts 0.76 vs. 0.92; P = 0.009), whereas SUVmax failed statistical significance (5.4 vs. 6.3 ng/ml/month; P = 0.08). Patients with a high SUVmax proved to have a significantly higher median Gleason score compared to low uptake 8.0 vs. 7.0; P = 0.004). Vice versa both SUVmax (GS 6: 5.0; GS 7: 5.6; GS 8: 5.7; GS 9: 6.5; r = 0.30, P = 0.008) and SUVts (GS 6: 0.63; GS 7: 0.68; GS 8: 0.85; GS 9: 0.89; r = 0.30, P = 0.006) significantly correlated with Gleason score. Patients with a Gleason score ≤ 3 + 4 had a significantly lower SUVmax (4.8 vs. 5.7; P = 0.02) and SUVts (0.67 vs. 0.85; P = 0.02) as compared to a Gleason score ≥ 4 + 3. Conclusion [11C]acetate uptake demonstrated to correlate with initial Gleason score. Furthermore, patients with a high PSA velocity proved to have higher [11C]acetate uptake in tumor lesions. Prostate 75:1760–1767, 2015. © 2015 Wiley Periodicals, Inc.